ANALYSIS OF POTENTIAL HAZARDS USING THE HIRARC METHOD (HAZARD IDENTIFICATION RISK ASSESSMENT AND RISK CONTROL) IN THE BAKERY MSME INDUSTRY AT IVAN BAKERY IN 2022 - Ratna Rambe; T. Samsul Hilal; Suroso Suroso (Jurnal Inovasi Penelitian, 2023)
Hazard identification Risk Assessment and Risk Control (HIRARC) is a method used to identify the value and level of risk of potential hazards in the workplace by identifying hazard characteristics that can occur and evaluating the impacts that occur using a risk assessment matrix. The purpose of this study is to identify potentials that can cause risks of harm in bread production. This research is a qualitative research to see the analysis of potential hazards using the HIRARC (Hazard Identification Risk Assessment And Risk Control) method in the breadmaking MSME industry with observational data collection techniques using the indepth interview method and using observation. This research was conducted in Kota Baru sub-district and was carried out in July 2022. The informants to be studied were 5 informants consisting of 4 workers and 1 owner. The results of the interview and observation found potential hazards in the workplace, namely, the risk of being pinched during the mixing process, the risk of respiratory problems due to / allergen flour, slippery floors, the risk of being slashed by a bread cutting tool, the risk of being squeezed in the dough grinding machine, the risk of burns, repetitive movements, the risk of being squeezed by the mixer, the hot room, the risk of being exposed to hot steam, the risk of being slashed by a knife during the material preparation process. In conclusion, based on the risk assessment of the potential dangers that exist in breadmaking at Ivan Bakery, it was found that several potential dangers of low risk levels are the risk of being squeezed by mixing / mixers, respiratory problems. Then for moderate risks are slippery floors, hot rooms, and slashed bread cutting tools. As for the high level of risk, namely repetitive movements.